STRATEGI PENANAMAN NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN PAI DI SMAN 2 PALANGKA RAYA - Priolawati, Melly; Normuslim, Normuslim; Gofur, Abdul (Jurnal Bilqolam Pendidikan Islam, 2025)
This study has a very important objective, namely to identify and analyze teacher strategies in the process of instilling multicultural education values ​​in Islamic Religious Education learning for class XII SMAN 2 Palangka Raya. To achieve this goal, the research used a qualitative method with data collection techniques used were in-depth interviews, participant observation and documentation. Then, the validity of the data was tested through triangulation of techniques and triangulation of sources. The results of the study showed that Islamic Religious Education teachers used six main strategies in instilling multicultural education values ​​in Islamic Religious Education learning, namely group learning/discussion strategies, meaningful learning strategies, experience-based learning strategies, learning strategies with humor, learning strategies using videos and ppts, and strategies to provoke student involvement. These strategies have proven effective in instilling multicultural education values ​​in Islamic Religious Education learning and have been proven to form students' attitudes that are more open, more tolerant, able to do good to fellow school residents who are diverse, and able to think critically about issues of diversity. The values ​​of multicultural education found in the Islamic Religious Education learning process include: tolerance values, moderation values, balance values, democratic values